THE INFLUENCE OF SHOPPING LIFESTYLE AND FLASH SALES ON IMPULSIVE BUYING BEHAVIOR AT SHOPEE E-COMMERCE FOR GENERATION Z IN EAST LUWU REGENCY - Madania, Sarah Putri; Purwanto, Sugeng (Yayasan Education and Social Center, 2024)
The purpose of this study was to determine the effect of shopping lifestyle and Flash Sales on impulsive buying behavior in shopee E-commerce for Generation Z in East Luwu Regency. This study uses quantitative research methods. The population studied was Shopee E-commerce users in East Luwu Regency, a sample of 108 people and the sampling technique used was a non-probability technique using purposive sampling. The data analysis technique uses the component-based Structural Equation Modeling (SEM) method using the Partial Least Square (PLS) analysis tool. The results showed that a shopping lifestyle has a positive and significant effect on impulsive buying and Flash Sales have a positive and significant effect on impulsive buying